PENGARUH BRAND IMAGE DAN PROMOSI TERHADAP LOYALITAS PELANGGAN PADA PENGGUNA PRODUK SKINCARE WARDAH DI KABUPATEN TASIKMALAYA - Ikmal Syabanul Haq; Nurherawati Nurherawati (Journal Economic Management and Business, 2026)
This study aims to analyze the influence of brand image and promotion on customer loyalty of Wardah skincare products in Tasikmalaya Regency. This research is motivated by the high use of skincare which is not always followed by loyalty to one particular brand so that consumers tend to switch brands. The method used is quantitative with a descriptive and verifiable approach. The research sample amounted to 85 respondents using purposive sampling techniques. Data were collected through questionnaires and analyzed using multiple linear regression, coefficient of determination (R²) test, and t-test. The results showed that brand image had a significant effect on customer loyalty with a significance value of 0.000 < 0.05 and t count 5.067 > 1.989. Promotion also had a significant effect with a significance value of 0.000 < 0.05 and t calculated 5.050 > 1.989. The R² value of 0.791 shows that customer loyalty is influenced by brand image and promotion by 79.1%.